Mental Lexicon and Memory Access: How Vocabulary is Stored in the Mind - Citra Tiurnida Panggabean; Muhammad Hasyimsyah Batubara (Journal of Advances in Linguistics and English Teaching (JALET), 2025)
This research aims to examine the structure and access of the mental lexicon in human memory through the psycholinguistic approach. The current study utilizes the qualitative descriptive approach by conducting a systematic literature review. The result shows that the access of the lexical knowledge is not constant, considering the frequency of the word, the contextual cue, and the meaning relationship, because it affects the language comprehension and production. The result also shows that the mental lexicon is hierarchically organized for effective lexical retrieval when people use language. This article concludes that the knowledge of the structure and the access of the mental lexicon is very significant for language acquisition processes and for the analysis of language disorders, including aphasia and dyslexia.